Hubungan Konsumsi Daging Merah dan Gaya Hidup Terhadap Risiko Kanker Kolon - Tahrir Aulawi (Kutubkhanah, 2013)
Cancer is a disease characterized by uncontrolled cell division and the ability of these cells to invade other tissues resulting in lysis. Cancer is the third cause of death in the world after cardiovascular diseases and respiratory, and gastrointestinal. Although the consumption of meat is not the only risk factor for colon cancer, but it remains a critically important point to note. Epidemiological and experimental studies indicate that the than fresh red meat and red meat consumption < 70 g/week will decrease 5-12% risk of cancer. Instead of protection against cancer promotion.